2023
DOI: 10.3389/fonc.2023.1094770
|View full text |Cite
|
Sign up to set email alerts
|

The whole treatment process and thinking of a patient with NUT carcinoma of the parotid gland: a case report

Abstract: BackgroundPrimary nuclear protein in testis (NUT) carcinoma is a rare malignant tumor originating from the salivary glands that usually occurs in midline structures, such as the head and neck, and has been identified in young patients. Progression of NUT carcinoma is rapid, and there is a high degree of malignant invasion. The median survival time of NUT carcinoma patients is 6 to 9 months, and 80% of the patients die within 1 year after diagnosis.Case descriptionThis case report summarizes the treatment of a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 24 publications
2
6
0
Order By: Relevance
“…The anatomical origin of HN‐NUT carcinoma is broad. Although sinonasal tract is the most commonly affected site, as documented in a previous systematic review 12 and in the current study, other reported sites of involvement included the thyroid gland, 7,18,19 major salivary glands (parotid, 14,15 submandibular 17,20,21 and sublingual 22 ), lacrimal gland, 14 larynx, 16 hypopharynx, 23 mandibular bone, 12 ear canal, 12 oral cavity, nasopharynx and neck soft tissue (current study). Although the median age of presentation of HN‐NUT carcinoma is in the 30s age range (37 years in a systematic review 12 and 39 years in the current study), the tumour may affect a wide age range, from 5 12 to 86 years (in the current study).…”
Section: Discussionsupporting
confidence: 66%
“…The anatomical origin of HN‐NUT carcinoma is broad. Although sinonasal tract is the most commonly affected site, as documented in a previous systematic review 12 and in the current study, other reported sites of involvement included the thyroid gland, 7,18,19 major salivary glands (parotid, 14,15 submandibular 17,20,21 and sublingual 22 ), lacrimal gland, 14 larynx, 16 hypopharynx, 23 mandibular bone, 12 ear canal, 12 oral cavity, nasopharynx and neck soft tissue (current study). Although the median age of presentation of HN‐NUT carcinoma is in the 30s age range (37 years in a systematic review 12 and 39 years in the current study), the tumour may affect a wide age range, from 5 12 to 86 years (in the current study).…”
Section: Discussionsupporting
confidence: 66%
“…As demonstrated by the current case and those reported in the literature, a misdiagnosis in a peripheral center is quite common. At the same time, the correct diagnosis is often reached only after a second opinion in a specialized high‐volume clinical institution 12–28 …”
Section: Discussionmentioning
confidence: 99%
“…We found 19 cases of NUTc arising from major salivary glands reported in the literature, with a timeframe ranging from 2009 to 2023. 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 (Tables 1 and 2 , Supplementary Table S1 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations